State of Indian agriculture : agricultural productivity, food security and climate change - Kumar, Sanjeev (New Delhi : SAGE Publications India Pvt Ltd, 2020)
Agriculture is a major source of rural employment and plays a crucial role in the economic development of India. The State of Indian Agriculture examines the present scenario of Indian agriculture and studies the trends at national as well as state level. The overall objective of the book is to analyze the impact of climate change on Indian agriculture and its implications for food security. The book recommends strategies to enhance productivity and the adoption of climate-smart practices to promote sustainable agriculture, thereby ensuring food security in India. It argues that there is an urgent need for a holistic and strategic approach to mitigate the challenges of climate change.
Keywords: Agriculture and state; Agricultural ecology; Food supply